1996
DOI: 10.1093/hmg/5.7.995
|View full text |Cite
|
Sign up to set email alerts
|

A model of mRNA splicing in adult lysosomal storage disease (glycogenosis type II)

Abstract: Glycogenosis type II is a recessively inherited disorder caused by mutations in the acid maltase (GAA) gene. Clinically, three different phenotypes are recognized: Infantile, juvenile and adult forms. A majority of compound heterozygous adult-onset patients carry a t-13g mutation in intron 1 associated with splicing out the first coding exon (exon 2). We have studied the mechanism of this mutation in a model system with wild-type and mutant minigenes expressed in a GAA deficient cell line. We have demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 31 publications
0
57
0
1
Order By: Relevance
“…All were compound heterozygous and shared the most common mutation associated with adult-onset disease in Caucasian patients, c.-32-13T → G. 25,26 None had been treated with recombinant enzyme. The clinical spectrum ranged from fatigability without muscle weakness to severe hypotonia, limited mobility, and wheelchair dependence.…”
Section: Resultsmentioning
confidence: 99%
“…All were compound heterozygous and shared the most common mutation associated with adult-onset disease in Caucasian patients, c.-32-13T → G. 25,26 None had been treated with recombinant enzyme. The clinical spectrum ranged from fatigability without muscle weakness to severe hypotonia, limited mobility, and wheelchair dependence.…”
Section: Resultsmentioning
confidence: 99%
“…30,32,33,35 It is worth mentioning that the mutation c.-32-13T4G, the most common one among the Caucasian LO GSDII patients, 3 has been previously studied in vitro using a minigene system assay. 51 The results have shown that this mutation does not completely prevent normal splicing, as low levels of the correctly spliced mRNA were generated with the mutant construct. In fact, three splice variants (SV1, SV2 and SV3-Table2) were observed with both the wild-type and the mutant constructs, indicating that these forms represent normal alternative spliced products.…”
Section: Resultsmentioning
confidence: 98%
“…The ethidium bromidestained gel bands were scanned and the signal intensities were quantified by the computerized Gel-Pro (version 3.1 for window 3). The ratio between the levels of the target gene amplification product and the β-actin (internal control) was calculated to normalize for initial variation in the sample concentration as a control for reaction efficiency ( Raben et al, 1996). All PCRs were independently replicated three times.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%